2023
DOI: 10.2903/j.efsa.2023.7884
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of N‐nitrosamines in food

Abstract: EFSA was asked for a scientific opinion on the risks to public health related to the presence of Nnitrosamines (N-NAs) in food. The risk assessment was confined to those 10 carcinogenic N-NAs occurring in food (TCNAs), i.e. NDMA, NMEA, NDEA, NDPA, NDBA, NMA, NSAR, NMOR, NPIP and NPYR. N-NAs are genotoxic and induce liver tumours in rodents. The in vivo data available to derive potency factors are limited, and therefore, equal potency of TCNAs was assumed. The lower confidence limit of the benchmark dose at 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 589 publications
(1,063 reference statements)
0
31
0
Order By: Relevance
“…The EFSA CONTAM Panel ultimately concluded that the MOEs calculated from the TCNA BMDL10s are below 10,000 in both scenarios, which raises a health concern. Attributing a lower potency factor to NMA, NDPA, NDBA, NSAR, NPIP, and NPYR would not change the above conclusion …”
Section: Nitrosamines In Foodreflections and Comparison To Pharmaceu...mentioning
confidence: 90%
See 1 more Smart Citation
“…The EFSA CONTAM Panel ultimately concluded that the MOEs calculated from the TCNA BMDL10s are below 10,000 in both scenarios, which raises a health concern. Attributing a lower potency factor to NMA, NDPA, NDBA, NSAR, NPIP, and NPYR would not change the above conclusion …”
Section: Nitrosamines In Foodreflections and Comparison To Pharmaceu...mentioning
confidence: 90%
“…Consequently, expert committees of the United Nations Food and Agriculture Organization (FAO) and the World Health Organization (WHO), as well as other UN bodies (e.g., the United Nations Environment Programme), have used the MOE approach . The Joint FAO/WHO Expert Committee on Food Additives (JECFA) routinely uses the MOE approach for assessing the risk of genotoxic and carcinogenic contaminants in foods. ,, …”
Section: Nitrosamines In Foodreflections and Comparison To Pharmaceu...mentioning
confidence: 99%
“…The report lists the median toxic doses (TD 50 ) for ten nitrosamine species as follows: NDMA (0.0959), NMEA (0.05), NDEA (0.0265), NDPA (0.186), NDBA (0.691), N-nitrosomethyl-n-alkylamine (NMA) (0.142), NMOR (0.109), NPIP (1.11), NPYR (0.799), and N-nitrososarcosine (NSAR) (0.982) (mg kg −1 body weight per day). 64 Acceptable amounts for nitrosamines are calculated based on TD 50 values. 65 In a study where acceptable intakes (AI) were determined for 11 N-nitrosamine species, acceptable intake levels of NDMA, NDEA, NDBA, NMOR, NMPA, NPIP, N-nitrosodiisopropylamine (DIPNA) and N-nitrosoethylisopropylamine (EIPNA) species were calculated based on TD 50 and 0.145, 62, 8.2, 0.129, 0.106, 1.33, 4.5-29 mg kg −1 and 4.1 mg kg −1 d −1 , respectively.…”
Section: Assessment Of N-nitrosamine Cancer Riskmentioning
confidence: 99%
“…However, nitrite addition is nowadays largely questioned by public health agencies, as it appears to be involved in the formation of various N -nitroso compounds (NOCs). Processed meat products preserved with nitrite and/or nitrate are associated with the occurrence of N -nitrosamines, some of which being genotoxic and classified as probable human carcinogenics . A large investigation of the Danish and Belgian markets indicated that the mean contents in nonvolatile N -nitrosamines (129 and 285 μg/kg) were 100-fold higher than those in volatile N -nitrosamines (1.6 and 2.9 μg/kg) in various processed products including bacon, ham, and salami .…”
Section: Introductionmentioning
confidence: 99%